The Impact of Reducing Psychiatric Beds on Suicide Rates - Atkinson, Jo-An; Page, Andrew; Skinner, Adam; Heffernan, Mark; Prodan, Ante; Hickie, Ian B. (Frontiers in Psychiatry, 2019)
There has been ongoing debate regarding the impact of reductions in psychiatric beds on suicide rates, and the potential effect of reallocation of acute hospital funding to community-based mental health programs and services. Computer simulation offers significant value in advancing such debate by providing a robust platform for exploring strategic resource allocation scenarios before they are implemented in the real world. We report an application that demonstrates a threshold effect of cuts to psychiatric beds on suicide rates and the role of context specific variations in population, behavioral, and service use dynamics in determining where that threshold lies. Findings have important implications for regional decision-making regarding resource allocation for suicide prevention.